Lack of Thy1 defines a pathogenic fraction of cardiac fibroblasts in heart failure. (April 2020) - Li, Yanzhen; Song, Daniel; Mao, Lan; Abraham, Dennis M.; Bursac, Nenad
Abstract: In response to heart injury, inflammation, or mechanical overload, quiescent cardiac fibroblasts (CFs) can become activated myofibroblasts leading to pathological matrix remodeling and decline in cardiac function. Specific targeting of fibroblasts may thus enable new therapeutic strategies to delay or reverse the progression of heart failure and cardiac fibrosis. However, it remains unknown if all CFs are equally responsive to specific pathological insults and if there exist sub-populations of resident fibroblasts in the heart that have distinctive pathogenic phenotypes. Here, we show that in response to transverse aortic constriction (TAC)-induced heart failure, previously uncharacterized Thy1 neg (Thy1-/MEFSK4+/CD45-/CD31-) fraction of mouse ventricular fibroblasts became more abundant and attained a more activated, pro-fibrotic myofibroblast phenotype compared to Thy1 Pos fraction. In a tissue-engineered 3D co-culture model of healthy cardiomyocytes and freshly isolated CFs, Thy1 neg CFs from TAC hearts significantly decreased cardiomyocyte contractile function and calcium transient amplitude, and increased extracellular collagen deposition yielding a profibrotic heart tissue phenotype. In vivo, mice with global knockout of Thy1 developed more severe cardiac dysfunction and fibrosis in response to TAC-induced heart failure than wild-type mice. Taken together, our studies identify cardiac myofibroblasts lacking Thy1 as a pathogenic CF fraction in cardiac fibrosis and suggest important roles of Thy1 in pathophysiology of heart failure.